Clinical Research Regarding the Ratio of Lymph Node Metastasis and the Reasonable Extent of Lymphadenectomy in Middle Third Thoracic Esophageal Squamous Cell Carcinoma - Ming-ran XIE, Peng LIN, Xu ZHANG; Ming-ran XIE, Peng LIN, Xu ZHANG; Ming-ran XIE, Peng LIN, Xu ZHANG (Cancer Biology & Medicine, 2010)
OBJECTIVE To explore the extent of lymphadenectomy deemed reasonable by analyzing the inﬂ uence of the regular pattern and ratio of lymph node metastasis on the prognosis of the patients with middle third thoracic esophageal squamous cell carcinoma. METHODS Clinical data from 129 patients with middle third thoracic esophageal squamous cell carcinoma who underwent curative esophagectomy with modern two-ﬁ eld lymphadenectomy were retrospectively analyzed. RESULTS The rate of lymphatic metastasis in EC patients was 56.6% in all groups, and the ratio of lymph node metastasis (RLNM, i.e. positive nodes/total dissected nodes) was 11.3%, with a lymphatic metastasis rate of 43.4% in the superior mediastinum. The most commonly involved regions included the sites around the esophagus, the right recurrent laryngeal nerve and the left-sided blood vessels of stomach, as well as the cardia and the inferior tracheal protuberance. The main factors influencing lymphatic metastasis were the depth of tumor infiltration, differentiation of tumor cells and the size of the tumor. The 5-year survival rate for patients in the groups without lymphatic metastasis, with a RLNM ≤ 20%, and a metastasis ratio > 20% was 50.4%, 31.0% and 6.8%, respectively. The differences were statistically significant among the groups (P = 0.000). CONCLUSION The RLNM is one of the key factors affecting the prognosis of EC patients. For conventional therapy for patients with middle third thoracic esophageal carcinoma, modern 2-field lymphadenectomy, including node dissection in the bilateral superior mediastinum, should be performed.